Batik wastewater treatment by nanoparticle Titanium Dioxide, TiO2 - S., Isrihetty; W. S., Wan Zaki; M. K., Ahmad; Hashim, Saim (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.